Influence of the organic loading rate on the growth of Galactomyces geotrichum in activated sludge - Matos, Maria F. (2012)
Recent studies reporting on the useful implementation of fungi in wastewater treatment plants triggered the need to improve fungi based systems. Therefore, it is crucial to investigate the conditions that promote their selection. The present work aims to study the effect of the organic loading rate on the growth of filamentous fungi. For this purpose, tThree sequencing batch reactors (SBR), fed with an easy biodegradable substrate (acetate), were operated at different organic loading rates: 4.3 g COD L-1 day-1 (SBR1), 1.0 g COD L-1 day-1 (SBR2) and 0.5 g COD L-1 day-1 (SBR3). High amounts of fungal filaments were observed in the SBR operating at higher organic loading rate, as ascertained by direct microscopic inspection, while, at lower organic loading rates, overabundance of fungal filaments was not observed. Sequence retrieved from the isolated fungal filaments presented high similarity (99 %) to Galactomyces geotrichum.